TYPES OF BIRDS IN THE AGRICULTURAL AREA OF PALAWIJA GUNONG PULO VILLAGE OF NORTH KLUET SUBDISTRICT SOUTH ACEH REGENCY - Lia Nur Afrija; Abdullah Abdullah; Devi Syafrianti; Khairil Khairil; Asiah M.D (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
The presence of birds in an area can explain the condition of the area. Birds can be an indicator of environmental quality and have an important role in supporting the survival of an organism's cycle. This research aims to find out the types of birds found in the agricultural area of Gunong Pulo Village, North Kluet Subdistrict, South Aceh Regency. Data collection was conducted in May 2021 by purposive sampling, with transect line observation methods and quantitative approaches. The results of the study were obtained by bird species located in the agricultural area of palawija namely Perkutut, Punai, Punai Gading, Purple Punai, Buckling, Red Bambangan, Red Cangak, Buffalo Egret, Large Egret, Kirik-kirik Biru, Lizard Selaya, Alang-alang, Kapasan Kemiri, Kite Fire, Red Woodpecker, Onion Woodpecker, Apung Sawah, Tiong Lampu Biasa, Tongtong Stork, Golden Tiong, Cica Small Leaf, Cipoh Kacat, Bido Snake Eagle, Bondol Eagle, Black Eagle, Finchang, Merbah Cerucuk, Red Chili, Hajj Bondol, Colorful Takur, and Black Kangaroo. From the results of the study can be concluded there are 32 species of bird species from 20 families observed in Gunong Pulo Village, North Kluet District of South Aceh Regency, based on the category of guild of insectivorous birds is the most common type, and based on habitat use, the family Ardeidae is a family with the most found individuals. Keywords: birds, waterbirds, guilds, habitats.Keberadaan burung pada suatu kawasan dapat menjelaskan kondisi dari kawasan tersebut. Burung merupakan indikator penting bagi kualitas lingkungan dan memiliki peran dalam mendukung keberlangsungan daur organisme. Penelitian ini bertujuan untuk mengetahui jenis-jenis burung yang terdapat di kawasan pertanian palawija Desa Gunong Pulo Kecamatan Kluet Utara, Kabupaten Aceh Selatan. Pengumpulan data dilakukan pada bulan Mei 2021 secara purposive sampling, dengan metode pengamatan line transek dan pendekatan kuantitatif. Hasil penelitian didapatkan spesies burung yang berada di kawasan pertanian palawija yaitu Perkutut, Punai, Punai Gading, Punai Ungu, Tekukur, Bambangan Merah, Cangak Merah, Kuntul Kerbau, Kuntul Besar, Kirik-kirik Biru, Kadalan Selaya, Bubut Alang-alang, Kapasan Kemiri, Layang-layang Api, Pelatuk Merah, Pelatuk Bawang, Apung Sawah, Tiong Lampu Biasa, Bangau Tongtong, Tiong Emas, Cica Daun Kecil, Cipoh Kacat, Elang Ular Bido, Elang Bondol, Elang Hitam, Kutilang, Merbah Cerucuk, Cabai Merah, Bondol Haji, Takur Warna-warni, dan kangkareng Hitam. Dari hasil penelitian dapat disimpulkan terdapat terdapat 32 jenis spesies burung dari 20 famili yang teramati berada di Desa Gunong Pulo Kecamatan Kluet Utara Kabupaten Aceh Selatan, berdasarkan kategori guild burung pemakan serangga merupakan jenis yang paling banyak dijumpai, dan berdasarkan penggunaan habitat, famili Ardeidae merupakan famili dengan individu paling banyak dijumpai.Kata kunci: burung, burung air, guild, habitat.